Case report: Focal heterotopic ossification in paravertebral muscles as a cause of neurogenic lameness in a dog - Hajek, Ivo; Rosati, Marco; Matiasek, Kaspar; Babinsky, Michal; Caine, Abby; Palus, Viktor (Frontiers in Veterinary Science, 2024)
This case report describes a 17-month-old Pudelpointer with recurring motor impairment localized to the left thoracic limb. Neurological exam highlighted lameness of that limb accompanied by prescapular swelling. Radiographs and magnetic resonance imaging detected an osseous structure in soft tissues close to the fifth cervical vertebra and subsequent surgery uncovered adjacent cervical spinal nerve impingement. Histology of the bony structure revealed heterotopic ossification in paravertebral muscles. Mild bone re-formation in operated site was detected after a 2-year period but the patient was asymptomatic. This article reports the first case of heterotopic ossification with spinal nerve entrapment in a dog and adds a new differential diagnosis to the causes of neurogenic lameness in dogs.